Obtaining and Investigation of the β-Cyclodextrin Inclusion Complex with Vitamin D3 Oil Solution - Ryszhan Bakirova; Altynbek Nukhuly; Ainara Iskineyeva; Serik Fazylov; Meiram Burkeyev; Ayaulym Mustafayeva; Yelena Minayeva; Akmaral Sarsenbekova (Scientifica)
Background. The research results of fat-soluble vitamin D3 (cholecalciferol) encapsulation with β-cyclodextrin have been presented in this work. The vitamin D3 inclusion complex with β-cyclodextrin was obtained under microwave radiation. The surface morphology of obtained clathrate inclusion complexes was described with the help of a scanning electron microscope. The thermographic measurement results on a differential scanning calorimeter have been presented. The activation energy of the β-cyclodextrin : vitamin D3 clathrate complex thermal oxidative destruction reaction was calculated. The clathrate thermal destruction kinetic parameters were determined. The inclusion complex spectral properties were characterized by IR-Fourier and 1H and 13C NMR spectroscopy. The existence of β-cyclodextrin inclusion complex with vitamin D3 in a 2 : 1 ratio was confirmed by the experimental results. The activation energy of thermal destruction of the inclusion complex of β-cyclodextrin with vitamin D3 was calculated using four different methods.